IMPROVING THE BALANCE IN CHILDREN OF 6-7 YEARS IN PHYSICAL EDUCATION LESSON THROUGH MUSIC MOVEMENT GAMES - Andreea - Gabriela Lazăr (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
In this research I started from the premise that music combined with different movements of the body or segments brings beneficial effects to children in the physical, mental and cognitive plane. Close collaboration between psychic and physical which involves the development of musical movement games can bring substantial contributions to child psychomotricity components. I considered the use of musical movement games in the case of children aged 6-7 years (the independent variable) may lead to a much faster increase of balance values compared to children in the control group. The aim of this research was to emphasize that balance can develop early. In this sense, we have introduced in the physical education and sports lessons a series of movement games made on music, to engage the active participation of the children and to contribute to the development of all forms of balance (static, dynamic and equilibrium of objects). The experiment was carried out on 14 children from the Gura Putnei Secondary School, aged between 6 and 7 years old. The control group consisted of 16 children from Secondary School "Stefan cel Mare" Putna. Within these schools I have been working as a teacher of physical education and sports, so I have been able to closely follow the evolution of children in both groups.